2016
DOI: 10.1038/srep39361
|View full text |Cite
|
Sign up to set email alerts
|

Public reporting as a prescriptions quality improvement measure in primary care settings in China: variations in effects associated with diagnoses

Abstract: The overprovision and irrational use of antibiotics and injections are a major public health concern. Public reporting has been adopted as a strategy to encourage good prescribing practices. This study evaluated the effects of public reporting on antibiotic and injection prescriptions in urban and rural primary care settings in Hubei province, China. A randomized control trial was conducted, with 10 primary care institutions being subject to public reporting and another 10 serving as controls. Prescription ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
1
13
1
Order By: Relevance
“…However, an audit and feedback plus the distribution of a pocket version of the guidelines increased the prescribing compliance in a Norwegian hospital in terms of the right choice of empirical antibiotics, appropriate treatment duration, and decreased use of high-dose benzyl penicillin [ 37 ]. Public reporting may also help enhance the effects of practice guidelines, albeit in a small effect size [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an audit and feedback plus the distribution of a pocket version of the guidelines increased the prescribing compliance in a Norwegian hospital in terms of the right choice of empirical antibiotics, appropriate treatment duration, and decreased use of high-dose benzyl penicillin [ 37 ]. Public reporting may also help enhance the effects of practice guidelines, albeit in a small effect size [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has resulted in a substantial loss of revenue for primary care facilities [ 41 , 42 ] due to a shortage of government subsidies. These facilities have to turn their attention to other avenues to compensate for the loss, including user charges for the parenteral administration of medicines [ 38 ]. The regional centralized procurement arrangement does not forfeit the autonomy of health facilities to decide what and how much they can spend on medicines [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public opinion/expectations and peer comparison appear to influence prescribing behaviours but in contrasting ways depending on the disease, patient cohort and doctor’s ranking. Liu et al [58], Tang et al [59], Tang et al [60], and Yang et al [61] reported effects of public reporting in primary care settings in China. Data on antibiotic prescribing (percentage of prescriptions including antibiotics or injections, and cost) were collected and individual doctors and facilities were compared and rankings were published publicly, e.g., on posters outside facilities.…”
Section: Table A1mentioning
confidence: 99%
“…Equitable access as devised through paradigms such as "accountability for reasonableness" (Daniels and Sabin 2002) is arguably more likely to enable and encourage relevant stakeholders -particularly the broader community -to be interested and proactively involved in national antibiotics policies and related infection prevention and control programmes. As we shall elaborate on below, an equitable regulatory lever is crucial in support bottom-up approaches to promoting high-value use of antimicrobials (Tang et al 2016).…”
Section: Ensuring Appropriate Affordable and Equitable Accessmentioning
confidence: 99%